Identifying self-regulated learning in chemistry classes – a good practice report - Feldman-Maggor Yael (Chemistry Teacher International, 2023)
Online learning has significantly evolved in recent years. Although it allows for greater flexibility, studies show that this flexibility also poses a challenge for individual learners who are required to manage their schedules and complete specific tasks independently. Therefore, success in an online learning environment relies heavily on the learner’s self-regulated learning (SRL) and ability to act independently and be active in the learning process. SRL is a dynamic ability that can be improved with proper guidance. This good practice report discusses a workshop that guides teachers to identify and enhance their students’ SRL. It focuses on engaging in learning processes while examining six SRL dimensions: goal setting, learning environment, learning strategy, time management, seeking help, and self-evaluation.